Pemanfaatan Pelepah Kelapa Sawit dengan Penambahan Limbah Kertas Kardus sebagai Bahan Pembuatan Kertas - Muhammad Fajriansyah; Ngatirah Ngatirah; Ida Bagus Banyuro Partha (Program Studi Teknologi Hasil Pertanian, 2025)
This study aims to determine the effect of mixing oil palm fronds and cardboard waste on the physical quality of paper, as well as to determine the most optimal mixture ratio and NaOH concentration.) The treatment consisted of NaOH concentrations (25%, 50%, 75%) and variations in the ratio of fronds: cardboard waste (1:1, 1:2, and 2:1). This study was analyzed using a 2-factor Complete Block Design. The parameters observed included water content, moisture factor, pulp yield, thickness, and absorbency. The results showed that the ratio / comparison of oil palm fronds and cardboard waste affected the analysis of water content, moisture factor and pulp yield, but did not affect the thickness and absorbency tests. The concentration of NaOH 25% affected the thickness and absorbency tests of paper. The ratio of oil palm fronds and cardboard waste 1; 2 affected the paper thickness test, while the ratio of oil palm fronds and cardboard waste 2; 1 affected the absorbency of paper.